Biomechanical basis of human movement - Hamill, Joseph, 1946-; Knutzen, Kathleen, ....- (Philadelphia : Lippincott Williams & Wilkins, 2003)
Biomechanical Basis of Human Movement integrates basic anatomy, physics, calculus, and physiology for the study of human movement. The book provides a uniquely quantitative approach to biomechanics, and is organized into three parts: Foundations of Human Movement, Functional Anatomy, and Mechanical Analysis of Human Motion. New to this edition: basic mathematics information, increased practical applications, and a new chapter on emphasizing techniques for measuring the strength of human tissue.
Contents: --------- I. FOUNDATIONS OF HUMAN MOVEMENT 1. Basic terminology 2. Skeletal considerations for movement 3. Muscular considerations for movement 4. Neurological considerations for movement II. FUNCTIONAL ANATOMY 5. The upper extremity 6. The lower extremity 7. The trunk III. MECHANICAL ANALYSIS OF HUMAN MOTION 8. Linear kinematics 9. Angular kinematics 10. Linear Kinetics 11. Angular Kinetics
Includes bibliographical references and index.
Keywords: Bewegingsleer; Biomechanica; Human mechanics; Kinesiologie